2008
DOI: 10.1105/tpc.108.058495
|View full text |Cite
|
Sign up to set email alerts
|

KNOXLost theOX: TheArabidopsis KNATMGene Defines a Novel Class of KNOX Transcriptional Regulators Missing the Homeodomain

Abstract: Three amino acid loop extension (TALE) homeodomain transcriptional regulators play a central role in plant and animal developmental programs. Plant KNOTTED1-like homeobox (KNOX) and animal Myeloid ecotropic viral integration site (MEIS) proteins share a TALE homeodomain and a MEINOX (MEIS-KNOX) domain, suggesting that an ancestral MEINOX-TALE protein predates the divergence of plants from fungi and animals. In this study, we identify and characterize the Arabidopsis thaliana KNATM gene, which encodes a MEINOX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
143
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(148 citation statements)
references
References 47 publications
(57 reference statements)
5
143
0
Order By: Relevance
“…To add further complexity to the network, a recently discovered KNOX protein lacking the DNA-binding domain competes for interacting factors (Magnani and Hake, 2008). Our results indicate that the induction of CUC1 is relatively specific to STM levels, although the closely related KNAT1 could also rapidly induce CUC1 when fused to the VP16 domain.…”
Section: Targets Of the Knoxi Transcription Factorsmentioning
confidence: 85%
“…To add further complexity to the network, a recently discovered KNOX protein lacking the DNA-binding domain competes for interacting factors (Magnani and Hake, 2008). Our results indicate that the induction of CUC1 is relatively specific to STM levels, although the closely related KNAT1 could also rapidly induce CUC1 when fused to the VP16 domain.…”
Section: Targets Of the Knoxi Transcription Factorsmentioning
confidence: 85%
“…Amino acid sequence comparison indicated that the FCL1 protein shares a high sequence similarity with the Arabidopsis KNATM-B (63% similarities and 43% identities) and tomato PTS/TKD1 (60% similarities and 48% identities), two recently identified class M homeodomainless KNOX proteins in Arabidopsis and tomato, respectively Magnani and Hake, 2008) (Figure 2H). Neighborjoining, maximum parsimony, and UPGMA phylogenetic tree (D) Orientation and exon-intron structures of 12 annotated ORFs within the common deletion region in fcl1-1 and fcl1-2 alleles.…”
Section: Truncatula Fcl1 Encodes a Class M Knox Proteinmentioning
confidence: 96%
“…It has been shown that the class M KNOX genes function to interfere with the canonical KNOXI activity by titrating proteinprotein interactions involving KNOXI and its interacting partners, BEL1-like (BELL) proteins, and by regulating nuclear localization of KNOXI-BELL complexes. However, the role of class M KNOXI in leaf development remains to be elucidated, since neither lossof-function mutants nor knockdown mutants have been isolated in Arabidopsis and tomato Magnani and Hake, 2008). Here, we report the isolation and characterization of loss-of-function fused compound leaf1 (fcl1) mutants from M. truncatula.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, a reduction in the expression of STM-like genes in compound-leafed species reduces leaf complexity (Hay and Tsiantis, 2006). The function of STM in leaf morphology is in part controlled by its interaction with the truncated form of the KNOX1 factor PETROSELINUM/KNOX ARABI-DOPSIS THALIANA MEINOX (PTS/KNATM) through competition for the formation of dimers with BEL-LIKE (BELL) homeodomain (HD) factors (Kimura et al, 2008;Magnani and Hake, 2008). KNOX1 levels also can be controlled at the network level by upstream factors in the PTS network module (Ichihashi et al, 2014).…”
mentioning
confidence: 99%